A method for preparing mesophase asphalt by catalysis using a promoter-Lewis acid system

By using the use of catalyst -lewis acid system during the process of asphalt preparation in the middle phase, improve the catalytic activity of Lewis acid, solve the difficulty of treatment caused by excessive amount of Lewis acid, and achieve the effect of efficient preparation in the middle phase asphalt.

CN115521802BInactive Publication Date: 2025-01-28BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211133075.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation of mesophase bitumen, excessive addition of Lewis acid catalyst leads to problems such as difficulty in post-treatment, difficult catalyst removal, and high equipment requirements.

Method used

Adopt a catalyst -lewis acid system, which can increase the catalytic activity of LEWIS acid through two types of two types: quality donor and carbon codes. High catalytic effect.

Benefits of technology

The middle phase asphalt is efficiently prepared under the amount of low LEWIS acid adding, which improves the optical content of the products of the product, and simplifies the removal of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115521802B_ABST
    Figure CN115521802B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing mesophase asphalt by catalysis of a co-catalyst-Lewis acid system, using raw material asphalt with low softening point, Lewis acid as main catalyst, acetic acid and isopropyl chloride as co-catalysts for catalytic polymerization. First, the Lewis acid and raw material asphalt are ground and evenly put into a customized reactor at a mass ratio of 6 to 12:100, and then the co-catalyst and Lewis acid are added to the reactor at a molar ratio of 4 to 60:100, and the reactor is kept at a constant temperature for 3-8 hours under the condition of 200-400°C. By adding a small amount of co-catalyst, the catalytic activity of Lewis acid can be improved, and in the case of low Lewis acid addition, a fused mesophase asphalt is directly generated in one step. The catalyst used in the present invention has good safety, is non-toxic and non-corrosive, and has a mild and convenient reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic preparation of mesophase asphalt, and specifically relates to a method for catalytic preparation of mesophase asphalt using a promoter-Lewis acid system. Background Art

[0002] Mesophase pitch is generally a nematic liquid crystal with a disc-like or rod-like molecular structure formed by the thermal condensation of heavy condensed aromatic hydrocarbons. Due to its good plasticity and processability, it is an excellent carbon material precursor and is widely used in fields such as mesophase pitch-based carbon fiber, needle coke, and lithium-ion secondary battery negative electrode.

[0003] At present, the preparation of mesophase asphalt is mainly based on thermal polycondensation. The raw asphalt is subjected to high-temperature pyrolysis to cause pyrolysis and polycondensation, and finally the mesophase asphalt is formed. The main factors affecting the formation of the mesophase asphalt are temperature, constant temperature time, raw material type, etc. By changing the temperature, constant temperature time, etc., mesophase asphalt with different physical and chemical properties can be prepared. The mesophase asphalt is prepared by direct polymerization. Since the asphalt raw material contains more aromatic substances and has good thermal stability, the heat treatment temperature is high and the constant temperature time is long when preparing the mesophase: the reaction at a temperature above 400°C can generate macromolecular aromatic compounds, but it is difficult to obtain high-quality products with low softening points by direct thermal polycondensation to prepare the mesophase asphalt.

[0004] Through research, it was found that adding AlCl in the reaction process of preparing mesophase asphalt by direct thermal polycondensation 3 , HF-BF 3 The Lewis acid catalyst can reduce the reaction temperature of the mesophase asphalt and shorten the heat preservation time. The mesophase asphalt with a lower softening point can be prepared at low temperature and short heat preservation time. Zheng Jiaming (Zheng Jiaming, Wang Chengyang, Ruan Xiangquan, Guo Chongtao. Preparation of naphthalene asphalt and mesophase asphalt by catalytic polycondensation [J]. Journal of Tianjin University, 1995 (02): 215-220.) used HF / BF in the patented catalytic polycondensation method to prepare naphthalene asphalt and mesophase asphalt. 3 As a catalyst, the system with refined naphthalene as raw material can easily prepare high-yield, isotropic naphthalene pitch: almost no dehydrogenation reaction occurs during the reaction, and naphthalene pitch contains a large amount of cycloalkyl hydrogen and some aliphatic hydrogen. 3 The boiling points of HF and BF are 19.9°C and -101.1°C, respectively. Therefore, after the reaction is completed, HF / BF can be almost completely removed from the resulting pitch by distillation and will not remain as solid contaminants. The synthesized naphthalene pitch is an excellent precursor for the mesophase pitch used to make carbon fibers. 3The corrosion of experimental equipment is very serious. This situation not only brings huge experimental safety problems, but also inevitably introduces some metal ions due to the corrosion of metal equipment by acid, which has an adverse effect on post-processing and product performance. Mochida added AlCl 3 As a catalyst (Preparation of nitrogen-rich pitches from diazanaphthalenes using AlCl 3 [J]. Carbon, 1996, 34: 601-608), first generate the precursor at low temperature, remove AlCl 3 After that, heat treatment is carried out in an inert gas atmosphere to obtain a mesophase pitch with good spinning performance. However, the 10%-50% catalyst addition makes the product mixed with a large amount of aluminum trichloride. After acid and alkali washing, it still exists in the form of aluminum oxide / hydroxide, and the content is huge, which has a certain impact on the mechanical properties of the material. Therefore, reducing AlCl 3 The amount added is very important.

[0005] Guo Jianguang's research shows that AlCl 3 When catalyzing the preparation of mesophase pitch, H 2 O as a co-catalyst and AlCl as the main catalyst 3 Proton donation, H + It interacts with the aromatic ring to reduce its electron cloud density and form positively charged hydrocarbon groups, which then initiate polymerization (Guo Jianguang. Preparation and performance research of naphthalene mesophase asphalt [D]. Hunan University, 2016). 2 When O is a promoter, AlCl 3 Before the substrate and H 2 O reacts to form Al(OH) 3 The insoluble substances are not conducive to the removal of catalysts. The present invention uses acetic acid, ethanol, isopropyl chloride, etc. as co-catalysts to avoid AlCl 3 The reaction generates Al(OH) 3 , which is conducive to subsequent removal.

[0006] In summary, adding catalysts in the process of preparing mesophase asphalt can effectively reduce the reaction conditions and increase the yield of mesophase asphalt. However, some problems are difficult to solve. By using a co-catalyst in the reaction process, the AlCl 3 catalytic activity and reduce Al(OH) 3 The formation of catalyst residues in the product can reduce the amount of catalyst residues in the product, and at low AlCl 3 When adding a certain amount, high AlCl3 The catalytic effect of the added amount. Summary of the invention

[0007] The present invention mainly aims at the problems existing in the process of preparing mesophase asphalt by Lewis acid catalysis, such as excessive addition of Lewis acid leading to difficulty in post-treatment, difficulty in catalyst removal, high equipment requirements, etc., and provides a method for combining Lewis acid with a co-catalyst, so that the catalytic effect of a high Lewis acid addition amount can be achieved under the condition of a low Lewis acid addition amount, thereby preparing mesophase asphalt with a high optical anisotropy content.

[0008] The technical solution adopted by the present invention to achieve the above-mentioned purpose is as follows:

[0009] A method for preparing mesophase asphalt by using a co-catalyst-Lewis acid system, using heavy aromatic hydrocarbons as raw materials, Lewis acid as main catalyst, acetic acid (HAc) or isopropyl chloride (iso-PrCl) as co-catalysts for catalytic polymerization, and directly preparing mesophase asphalt in one step.

[0010] The specific steps include the following:

[0011] Step 1): using heavy asphalt as raw material, first drying the raw asphalt and Lewis acid to achieve an anhydrous state;

[0012] Step 2) in an inert gas atmosphere, weigh Lewis acid and raw asphalt in a material mass ratio of 6 to 12:100, mix them evenly, and then load them into a high-pressure reactor;

[0013] Step 3): adding a promoter to a reaction kettle, wherein the molar ratio of the promoter to the Lewis acid is 4 to 50:100;

[0014] Step 4): After closing the reactor, place it in a constant temperature device, heat it to 200-400° C., and keep it at this temperature for 3-8 hours;

[0015] Step 5): After the reaction is completed, the product is allowed to stand at room temperature, and then taken out and ground into powder, and then washed with hydrochloric acid and sodium hydroxide to remove Lewis acid and obtain mesophase asphalt;

[0016] The heavy aromatics (coal tar pitch) include coal tar pitch, petroleum aromatic heavy oil or asphalt, synthetic asphalt, model aromatics, etc.

[0017] The Lewis acid is AlCl 3 、FeCl 3 、ZrCl 4 One of them.

[0018] The promoter in step 3 is acetic acid, isopropyl chloride or isopropyl bromide.

[0019] Compared with the prior art, the present invention has the advantage of using a co-catalyst-Lewis acid catalytic system, wherein the co-catalyst has two types: a proton donor and a carbon cation donor. The proton donor provides protons H to the Lewis acid. + , proton H + Attacking the aromatic ring reduces the electron cloud density on the aromatic carbon atom and forms carbon cations, which then initiate polymerization to form macromolecular aromatic ring polymers; while the carbon cation donor coordinates with the Lewis acid to form highly active carbon cation groups, which attack the benzene ring to initiate polymerization. A very small amount of co-catalyst can improve the catalytic activity of the main catalyst Lewis acid, so that in the case of low Lewis acid addition, the one-pot reaction can achieve the catalytic effect of high catalyst addition and increase the formation ratio of mesophase asphalt. At the same time, since there is no water in the system, it will not react with Lewis acid to form insoluble metal compounds, which is conducive to the removal of Lewis acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are polarization diagrams corresponding to the embodiments of the present invention and the comparative examples.

[0021] Figure 1 , Medium temperature coal tar pitch 370℃ 8% AlCl 3 0.02 ml acetic acid 5 h

[0022] Figure 2 , Medium temperature coal tar pitch 370℃ 8% AlCl 3 0.02 ml acetic acid 8h

[0023] Figure 3 , Medium temperature coal tar pitch 370℃ 8% AlCl 3 0.06 ml acetic acid 8h

[0024] Figure 4 , Medium temperature coal tar pitch 370℃ 8% AlCl 3 0.06ml iso-PrCl 8h

[0025] Figure 5 , Medium temperature coal tar pitch 370℃ 8% ZrCl 4 0.06ml iso-PrCl 8h

[0026] Figure 6 、Naphthalene asphalt 370℃ 6% AlCl 3 0.015 ml acetic acid 8 h

[0027] Figure 7 、Naphthalene asphalt 370℃ 6% AlCl 3 8h

[0028] Figure 8 , Medium temperature coal tar pitch 250℃ 6% AlCl 3 8h

[0029] Fig. 9 , Medium temperature coal tar pitch 370℃ 8% AlCl 3 8h

[0030] Fig.10 , Medium temperature coal tar pitch 370℃ 8% ZrCl 4 8h

[0031] Fig.11 , Medium temperature coal tar pitch 370℃ 12% AlCl 3 8h DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0033] Example 1

[0034] Medium-temperature coal tar pitch with a softening point of 85°C and an ash content of less than 0.3% was used as the raw material. 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw asphalt was weighed in a material mass ratio of 8:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst acetic acid (HAc) was injected into the reactor, and the co-catalyst and Lewis acid AlCl 3 The molar ratio of is 1:5, the reactor is closed and placed in a constant temperature device, the constant temperature is 370℃, and the constant temperature time is 5h; after the reaction is completed, it is allowed to stand at room temperature, the product is taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 1 ).

[0035] Example 2

[0036] Medium-temperature coal tar pitch with a softening point of 85°C and an ash content of less than 0.3% was used as the raw material. 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw asphalt was weighed in a material mass ratio of 8:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst acetic acid (HAc) was injected into the reactor, and the co-catalyst and Lewis acid AlCl 3The molar ratio of is 1:5, the reactor is closed and placed in a constant temperature device, the constant temperature is 370℃, and the constant temperature time is 8h; after the reaction is completed, it is allowed to stand at room temperature, the product is taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 2 ).

[0037] Example 3

[0038] Medium-temperature coal tar pitch with a softening point of 85°C and an ash content of less than 0.3% was used as the raw material. 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw asphalt was weighed in a material mass ratio of 8:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst acetic acid (HAc) was injected into the reactor, and the co-catalyst and Lewis acid AlCl 3 The molar ratio of is 3:5, the reactor is closed and placed in a constant temperature device, the constant temperature is 370℃, and the constant temperature time is 8h; after the reaction is completed, it is allowed to stand at room temperature, the product is taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 3 ).

[0039] Example 4

[0040] Medium-temperature coal tar pitch with a softening point of 85°C and an ash content of less than 0.3% was used as the raw material. 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw material asphalt was weighed in a material mass ratio of 8:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst isopropyl chloride (iso-PrCl) was injected into the reactor, and the co-catalyst and Lewis acid AlCl 3 The molar ratio of is 3:5, the reactor is closed and placed in a constant temperature device, the constant temperature is 370℃, and the constant temperature time is 8h; after the reaction is completed, it is allowed to stand at room temperature, the product is taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 4 ).

[0041] Example 5

[0042] Medium-temperature coal tar pitch with a softening point of 85°C and an ash content of less than 0.3% was used as the raw material. 4 Drying treatment to achieve anhydrous state. 2 ZrCl 4The raw material asphalt was weighed in a material mass ratio of 8:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst isopropyl chloride (iso-PrCl) was injected into the reactor, and the co-catalyst and Lewis acid ZrCl 4 The molar ratio of is 3:5, the reactor is closed and placed in a thermostat, the constant temperature is 370℃, and the constant temperature time is 8h. After the reaction is completed, the product is taken out and ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 5 ).

[0043] Example 6

[0044] Using naphthalene asphalt with a softening point of 150℃ as raw material, naphthalene asphalt and Lewis acid AlCl 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw asphalt was weighed in a material mass ratio of 6:100 and ground into a mortar to 200 mesh, and then loaded into the reactor; the co-catalyst acetic acid (HAc) was injected into the reactor, and the co-catalyst and Lewis acid AlCl 3 The molar ratio of is 1:5, the reactor is closed and placed in a constant temperature device, the constant temperature is 370℃, and the constant temperature time is 8h; after the reaction is completed, it is allowed to stand at room temperature, the product is taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused mesophase asphalt (attached Figure 6 ).

[0045] Example 7

[0046] Using naphthalene asphalt with a softening point of 150℃ as raw material, naphthalene asphalt and Lewis acid AlCl 3 Drying treatment to achieve anhydrous state. 2 AlCl 3 The raw material asphalt was weighed in a material mass ratio of 6:100 and ground into a mortar to 200 mesh, then loaded into a reactor, and the reactor was closed and placed in a constant temperature device with a constant temperature of 370°C for 8 hours. After the reaction was completed, the product was allowed to stand at room temperature, taken out, ground into powder, and washed with hydrochloric acid-sodium hydroxide solution to obtain a fused intermediate phase asphalt (attached Figure 7 ).

[0047] Comparative Example 1

[0048] Compared with Example 1, the reaction temperature was lowered to 250°C, the proportion of Lewis acid catalyst was lowered to 6%, no co-catalyst was added, and the reaction time was extended to 8h. The raw materials and other reaction conditions remained unchanged. Finally, an isotropic asphalt (attached Figure 8), no anisotropic mesophase pitch is produced.

[0049] Comparative Example 2

[0050] Compared with Examples 2, 3, and 4, no co-catalyst acetic acid (HAc) was added, and the raw materials and other reaction conditions remained unchanged, and finally a carbon microsphere-type mesophase pitch (attached Fig. 9 ).

[0051] Comparative Example 3

[0052] Compared with Example 5, the catalyst iso-PrCl was not added, the raw materials and other reaction conditions remained unchanged, and finally the carbon microsphere mesophase pitch (attached Fig.10 ).

[0053] Comparative Example 4

[0054] Compared with Examples 2, 3, 4 and 5, no promoter was added, the content of aluminum chloride was increased, the raw materials and other reaction conditions remained unchanged, and finally a fused mesophase pitch (attached Fig.11 ).

[0055] Statistics

[0056] raw material Temperature ℃ Main Catalyst Catalyst Constant temperature time Example 1 Medium temperature coal tar 370 <![CDATA[8%AlCl 3 ]]> Acetic acid 5h Example 2 Medium temperature coal tar 370 <![CDATA[8%AlCl 3 ]]> Acetic acid 8h Example 3 Medium temperature coal tar 370 <![CDATA[8%AlCl 3 ]]> Acetic acid 8h Example 4 Medium temperature coal tar 370 <![CDATA[8%AlCl 3 ]]> Isopropyl Chloride 8h Example 5 Medium temperature coal tar 370 <![CDATA[8%ZrCl 4 ]]> Isopropyl Chloride 8h Example 6 Naphthalene Asphalt 370 <![CDATA[6%AlCl 3 ]]> Acetic acid 8h Example 7 Naphthalene Asphalt 370 <![CDATA[6%AlCl 3 ]]> none 8h Comparative Example 1 Medium temperature coal tar 250 <![CDATA[6%AlCl 3 ]]> none 8h Comparative Example 2 Medium temperature coal tar 370 <![CDATA[8%AlCl 3 ]]> none 8h Comparative Example 3 Medium temperature coal tar 370 <![CDATA[8%ZrCl 4 ]]> none 8h Comparative Example 4 Medium temperature coal tar 370 <![CDATA[12%AlCl 3 ]]> none 8h

[0057] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A method for preparing mesophase asphalt using a promoter-Lewis acid system, characterized in that Prepared by the following method: Step 1): firstly drying the raw material asphalt and Lewis acid to achieve anhydrous state; Step 2): Lewis acid and raw asphalt are weighed in a certain mass ratio, mixed evenly, and loaded into a reaction kettle. The entire operation is carried out under a dry inert atmosphere; Step 3): adding a certain amount of co-catalyst into the reaction kettle under an inert environment; Step 4): Seal the reactor, increase the temperature, and perform a thermal polycondensation reaction; Step 5): After the reaction is completed, the product is allowed to stand at room temperature, and then the product is taken out and ground into powder, and then washed with hydrochloric acid and sodium hydroxide to obtain mesophase asphalt; As mentioned above, the Lewis acid is one of AlCl3, FeCl3, and ZrCl4, and the co-catalyst is one of acetic acid, isopropyl chloride, and isopropyl bromide.

2. A method for preparing mesophase pitch by catalysis using a co-catalyst-Lewis acid system as claimed in claim 1, characterized in that: The raw material asphalt is one of coal tar, petroleum heavy oil, petroleum asphalt, synthetic asphalt, naphthalene, anthracene, phenanthrene or a mixture thereof.

3. A method for preparing mesophase pitch by catalysis using a co-catalyst-Lewis acid system as claimed in claim 1, characterized in that: The reaction temperature is 200-400° C., and the reaction time is 3 h to 8 h.

4. A method for preparing mesophase pitch by catalysis using a co-catalyst-Lewis acid system as claimed in claim 1, characterized in that: The mass ratio of Lewis acid to raw asphalt is 6-12:100; the molar ratio of co-catalyst to Lewis acid is 4-60:100.